Assessment of the water quality of the upper reaches of the ouémé river in benin using benthic macroinvertebrate-based biotic indices - Abahi, Koudjodé; Gouissi, Modeste; Akodogbo, Hotèkpo; Sanni Worogo, Sorébou; Adje, Ayodélé Shola; Gnohossou, Pierre (Revue des Sciences de l’Eau / Journal of Water Science, 2020)
To cope with the numerous consequences of stream pollution caused by anthropogenic activities, it is necessary to evaluate the water quality for sustainable management. The present study aims to evaluate the water quality of the upper reaches of the Ouémé River in Benin using biotic indices based on benthic macroinvertebrates. Macroinvertebrates were sampled using a Surber net in four stations distributed over the longitudinal profile of the upper reaches of the Ouémé River. After sample collection, the macroinvertebrates were separated, identified and counted under a stereo-microscope. A total of 13 macroinvertebrate orders and 24 macroinvertebrate families were collected in this study. The Chironomidae was the most abundant family. The results of the Ephemeroptera, Plecoptera, Trichoptera (EPT) Index, the EPT/Chironomidae Index, the Hilsenhoff Index and the Standardized Global Biological Index (IBGN) revealed that the Upper Ouémé River has very poor water quality. The intense pressures from human activities in this part of the river have led to serious organic pollution, which has resulted in the proliferation of macroinvertebrates resistant to pollution to the detriment of those sensitive to pollution. On the basis of this result, protection and recovery measures must be taken to preserve and improve the ecological status of the waters of the upper reaches of the Ouémé River.